Unpacking the Public Private Partnership Revival - Bayliss, Kate; Van Waeyenberge, Elisa (The Journal of development studies, 2018)
This paper examines the recent resurgence of interest in public-private partnerships (PPPs) to provide infrastructure in developing countries. First, the paper demonstrates that there has been a revival of support for private sector participation in infrastructure. Second, the paper argues that this revival differs from earlier attempts to increase the involvement of the private sector in public service provision in a number of respects. In particular, the current support for PPPs is related to an increased availability of global financial capital. Third, the paper considers the implications of this distinct feature of the revival for development.